Waste Vegetable Oil: A Boon for Biodiesel Production - Kavita, H S; Krishnamurthy, V.; Chandra Prabha, M N; Roshan, Makam (Kathmandu University Journal of Science, Engineering and Technology, 2015)
Edible Waste Vegetable Oils (WVO) pose a potential threat to water quality, putting pressure on community water treatment facilities due to their recalcitrant nature. Repurposing them as feedstocks for biodiesel production through the trans-esterification process offers a sustainable solution to address water pollution while meeting the rising demand for fuel. This study aimed to synthesize biodiesel from WVO using an indigenously designed, modular, and mobile biodiesel reactor plant capable of producing 40 liters of biodiesel per day. The biodiesel obtained underwent standard fuel tests, and the results aligned well with the corresponding ASTM standards, ensuring quality and reliability. With a cost of just thirty rupees per liter, the biodiesel proved to be economically viable. Field tests were conducted to evaluate its performance, including blending it at a 20% level with commercial diesel in heavy motor vehicle fuel tanks and using it as a boiler oil fuel for water heating. Additionally, the incidental by-product, glycerol, was found to have commercial value, further enhancing the sustainability of the biodiesel production process.